Formal Techniques for Safety-Critical Systems 4th International Workshop, FTSCS 2015, Paris, France, November 6-7, 2015. Revised Selected Papers - Artho, Cyrille; Ölveczky, Peter Csaba (Communications in Computer and Information Science, 2016)
This book constitutes the refereed proceedings of the 4th International Workshop on Formal Techniques for Safety-Critical Systems, FTSCS 2015, held in Paris, France, in November 2015. The 15 revised full papers presented together with one invited talk and two tool papers were carefully reviewed and selected from 41 submissions. The papers are organized in topical sections on timed systems; railway systems; fault tolerance; automotive systems; software and systems analysis; tools. .